Join Sarthaks eConnect Today - Largest Online Education Community!
0 votes
10 views
asked in Mathematics by (67k points)
edited by

Let α ,β ,γ be the roots of the equation x+ 4x + 1 = 0, then (α + β)-1 + (β + γ)-1 + (γ + α)-1 equals

(a)  2

(b)  3

(c)  4

(d)  5

1 Answer

+1 vote
answered by (62.1k points)
selected by
 
Best answer

Correct option   (c) 4

Explanation:

α + β + γ  = 0, α β + β  γ + γ α = 4, α β γ = -1

1/α + β + 1/β + γ + 1/γ + α = 1/γ - 1/α - 1/β

= - α β + β γ +  γ α/αβγ = (4/-1) = 4

Related questions

Welcome to Sarthaks eConnect: A unique platform where students can interact with teachers/experts/students to get solutions to their queries. Students (upto class 10+2) preparing for All Government Exams, CBSE Board Exam, ICSE Board Exam, State Board Exam, JEE (Mains+Advance) and NEET can ask questions from any subject and get quick answers by subject teachers/ experts/mentors/students.

One Thought Forever

“There is a close connection between getting up in the world and getting up in the morning.“
– Anon
~~~*****~~~

Categories

...